The Influence of Resource-based Learning Model based on Flashcard toward Students’ Problem-Solving Abilities - Angelica, Debbi; Novitasari, Aulia (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2020)
The purpose of this research was to determine the influence of the Resource-based learning model (RBL) based on flashcards on students’ problem-solving abilities and motivation. The design of this research quasi-experimental with a posttest only control group design. The data analysis techniques employed in this research were the normality test using the Lilifors test and the MANOVA test to determine the hypothesis. Based on the analysis, the MANOVA test to determine the average score difference of students’ problem-solving abilities in the experimental class and the control class obtained a sig value of 0.00 so that sig. 2 (tailed) ≤ 0.05 which indicated that H0 was rejected and Hi was accepted. Therefore, it can be concluded that the Resource-based learning model (RBL) based on flashcards influenced the students’ problem-solving abilities and learning motivation.